The Effect of Service Quality, Price Perception, and Promotion Strategies on Consumer Buying Interest (Study on Takoyaki Msmes) - Iffah Robiatul Muflika; Imam Syairozi; M. Yaskun (Sean Institute, 2024)
This study aims to analyze the influence of service quality, price perception, and promotion strategies on consumer buying interest in Takoyaki MSMEs in Sugio District, Lamongan. The research uses a quantitative approach with a survey method. The study population amounted to 280 consumers and the sample was determined using the Slovin formula so that 74 respondents were obtained. Primary data were collected through a Likert scale-based questionnaire and analyzed using IBM SPSS Statistics 25. The results of the study showed that the quality of service had a positive and significant effect on consumer buying interest with a tcal value of 2,450 > a table of 1,994 and a significance value of 0.000 < 0.05. Price perception also had a positive and significant effect with a tcal value of 2.782 > a ttable of 1.994 and a significance value of 0.000 < 0.05. The promotion strategy had a positive and significant effect with a tcal value of 3.629 > a ttable of 1.994 and a significance value of 0.000 < 0.05. Simultaneously, the three variables had a positive and significant effect on consumer buying interest with a Fcal value of 25.914 > Ftable of 2.74 and a significance of 0.000 < 0.05. The value of the R Square determination coefficient of 0.549 showed that service quality, price perception, and promotional strategy were able to explain the variation in consumer buying interest by 54.9%, while the rest was influenced by other factors outside the research model.